A case report of complete cricotracheal separation: An experience from the east coast of Malaysia - Rozhan, 'Atikah; Mohamad, Adam; M. Rajet, Khairul Azhar; Ahmad, Mohd Zaki; Bin Yusof, Suhaimi; Wan Mohamed, Wan Emelda; Susibalan, Bathma Devi; Nik Abd Ghani, Nik Mohd Syukra; Bin Asha’ari, Zamzil Amin (The Korean Society of Traumatology, 2022)
Complete cricotracheal separation, which is the most severe type of laryngeal trauma, is an uncommonly seen injury that clinicians have limited experience in managing. However, it is potentially fatal. Due to limited exposure to this condition, mismanagement can occur, which may further aggravate the patient’s condition. The most crucial part of managing this injury is to establish a secure airway. Tracheostomy under local anesthesia is the preferred method of airway stabilization, in order to avoid further injuries to the airway caused by endotracheal intubation. Here, we discuss the management of complete cricotracheal separation based on a case experienced in the east coast region of Malaysia, where this type of injury is rarely encountered.